Geomagnetic effects on cosmic ray propagation for different conditions - Masías-Meza, J.J. (2011)
The geomagnetic field (B geo) sets a lower cutoff rigidity (R c) to the entry of cosmic particles to Earth which depends on the geomagnetic activity. From numerical simulations of the trajectory of a proton (performed with the MAGCOS code) in the B geo, we use backtracking to analyze particles arriving at the Auger Observatory location. We determine the asymptotic trajectories and the values of R c in different incidence directions. Simulations were done using several models of B geo that emulate different geomagnetic conditions. © 2012 International Astronomical Union.